2013
DOI: 10.1038/ncomms3247
|View full text |Cite
|
Sign up to set email alerts
|

A poly(A)-specific ribonuclease directly regulates the poly(A) status of mitochondrial mRNA in Arabidopsis

Abstract: Coordination of gene expression in the organelles and the nucleus is important for eukaryotic cell function. Transcriptional and post-transcriptional gene regulation in mitochondria remains incompletely understood in most eukaryotes, including plants. Here we show that poly(A)-specific ribonuclease, which influences the poly(A) status of cytoplasmic mRNA in many eukaryotes, directly regulates the poly(A) tract of mitochondrial mRNA in conjunction with a bacterial-type poly(A) polymerase, AGS1, in Arabidopsis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 48 publications
1
66
1
1
Order By: Relevance
“…Next, we analyzed the effect of ABA on epidermal cells in aba hypersensitive germination ( ahg ) mutants, which show a hypersensitivity to ABA during germination and early seedling growth414243444546. The ahg1-1 , ahg2-1 and ahg3-1 mutants grown in the presence of ABA exhibited enhanced ectopic outgrowth and produced larger numbers of protrusions than the wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we analyzed the effect of ABA on epidermal cells in aba hypersensitive germination ( ahg ) mutants, which show a hypersensitivity to ABA during germination and early seedling growth414243444546. The ahg1-1 , ahg2-1 and ahg3-1 mutants grown in the presence of ABA exhibited enhanced ectopic outgrowth and produced larger numbers of protrusions than the wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the specific function of AHG1 and AHG3 in seed germination and early growth is well correlated with the requirement of ABA during germination and the early phase of seedling growth for ectopic outgrowth to occur. AHG2 encodes the polyA-specific ribonuclease (PARN) that modulates ABA and salicylic acid signaling via mitochondrial RNA metabolism424546. The PP2Cs and AHG2-dependent pathway might be coordinately involved in ABA-dependent ectopic outgrowth in epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, several previous studies have clearly shown that deadenylases are required for the development and stress response of plants. For example in Arabidopsis thaliana, PARN is essential for embryogenesis [6,7], response to abscisic acid and salicylic acid [8,9] as well as mitochondrion functions [10]. Caf1 is involved in the responses to both biotic and abiotic stresses in Capsicum annuum, Arabidopsis thaliana and Oryza sativa [11][12][13][14].…”
Section: Page 3 Of 26mentioning
confidence: 99%
“…1 This necessitates tightly coordinated gene expression between the nuclear and organellar genomes. 8 This finding is surprising given that PARN is distributed widely among eukaryotes (other than budding yeast and Drosophila 9 ) and has been shown to regulate the poly(A) status of cytoplasmic RNA in various organisms, but never in organelles. [2][3][4] Although neither signaling system has been fully elucidated, they are thought to involve regulation at the levels of transcription, post-transcription, and post-translation, in both the nucleus and organelles.…”
Section: Introductionmentioning
confidence: 99%